SMM promotion of tourism - Abduova, M.N.; Seidualin, D.A.; Rustemova, S.M. (BUKETOV BUSINESS REVIEW, 2023)
Object: The purpose of this work is to identify the features of SMM tools and how to use them to promote tourism services in modern conditions. Methods: This study includes an analysis of the promotion of a number of travel companies through social media tools. Results: The article discusses SMM tools and methods of their application for the promotion of tourist services in modern conditions. In the age of globalization of the information space, when the Internet has covered almost all spheres of activity, tourism has received a new opportunity to promote its product. After all, today the Internet is not only a form of communication, but also an indispensable tool for the delivery and maintenance of information, business development. Social networks play a special role, thanks to which a new market is developing with all the necessary technological and social conditions. The tools utilized by social networks, along with their operational mechanisms, enable a specific tourism company to distinguish itself from the sea of competitors. This results in lowered expenses for online advertising, heightened customer loyalty, and the attraction of fresh clientele. In a global context, social networks can become a tool for creating a positive image of the country, redistributing tourist flows, and forming an information base for tourists. Conclusions: Despite all the positive aspects of social networks, the study identified significant problems that negatively affect the development of tourism. These factors include: fraud, distortion of reality, the authority of the opinion of media personalities, uneven coverage of age groups of tourists. These and possible other problems today require special attention and require a set of measures for advertising and promotion in social media.